Elevated blood tantalum concentrations in patients following reconstruction of severe acetabular defects in total hip arthroplasty using modular tantalum augments in combination with uncemented tantalum cups - Spranz, David Maximilian; Müller, Lisa-Marie; Trefzer, Raphael; Hetto, Pit; Innmann, Moritz Maximilian; Renkawitz, Tobias; Walker, Tilman; Reiner, Tobias (The journal of arthroplasty, 2024)
Background - The reconstruction of acetabular defects in total hip arthroplasty (THA) can be challenging. An option to treat uncontained acetabular defects is to use modular tantalum augments in combination with cementless press-fit cups. However, modularity is associated with an increased risk of debonding and mechanical failure. In addition, metal wear particles can be released due to micromotions at the implant interface. Clinical data on the long-term results of this treatment strategy is limited. The purposes of this study were: (1) to evaluate the clinical and radiological outcome of complex THA using modular trabecular metal augments and uncemented revision cups; (2) to investigate the blood tantalum concentrations in these patients at mid-term (mean 4.5 year) follow-up; and (3) to report complications and mechanisms of failure related to this procedure. - Methods - In this single-center study, we retrospectively reviewed data from a consecutive cohort of 27 patients who underwent complex acetabular defect reconstruction using a modular tantalum acetabular augment in combination with an uncemented tantalum cup. We evaluated the implant survival, and the radiological and clinical outcomes after a mean follow-up of 4.5 years (standard deviation 2.1; range 2.5 to 10.6 years) using patient-reported outcome scores. Blood samples were analyzed regarding tantalum concentration and compared with a control group. - Results - The cumulative survival rate at 4.5 years with the end point “revision of the acetabular component for aseptic loosening” was 94.4% (95% confidence interval [CI] 71.6 to 99.2) and 82.9% (95% CI 60.5 to 93.3) for the end point “revision for any reason.” The patient-reported outcome scores improved significantly up to the latest follow-up, and radiographic data showed no signs of loosening or implant migration. Median blood tantalum concentrations were significantly higher in the study group (0.15 μg/L) compared to the control group (0.002 μg/L) (P < .001). - Conclusions - This study demonstrated acceptable clinical and radiological results of cementless revision THA using modular trabecular metal implants for the reconstruction of large acetabular defects. Tantalum concentrations were significantly higher in patients who had tantalum implants compared to the control group; however, the systemic and local effects of an increased tantalum exposure are not yet fully understood and have to be further investigated.